Środowisko prawników wobec sytuacji Trybunału Konstytucyjnego. Badania socjologiczno-prawne - Stępniak, Kamil (Studia Prawa Publicznego, 2019)
The recent legal changes pertaining to the institution of the Constitutional Tribunal arouse many controversies. This paper presents a sociological and legal study conducted to collect and examine the opinions regarding the above held by Polish lawyers who because of their profession and experience are in a position to confront directly the legal practice with the changing legal system that is directly responsible for the level of protection of individual rights and the exercise of individual fundamental rights. From the point of view of rationality and functionality of the operations of the Constitutional Tribunal an opinion formulated by jurists who due to their background have greater legal awareness seemed invaluable. After all it will be their opinion which will decide about the future of the judiciary in Poland. The results of the current transformations being implemented in constitutional judiciary as well as at the level of common courts have consequences for all the citizens. The aim of the questions asked in the survey was to ﬁ nd how lawyers in Poland saw the situation with the Constitutional Tribunal today as well as what the though it its regime and functioning could be like in the future. Questions also concerned the current and actual legal status of the Tribunal and the lawyers’ reactions to the changes being implemented or about to me made, and if possible the possible ways of ending the current Constitutional Tribunal crisis.